Mood analysis and self-correction to enhance EFL students’ grammatical accuracy - Katharina Rustipa; Endang Yuliyani Rahayu; Yulistiyanti Yulistiyanti (EduLite: Journal of English Education, Literature and Culture, 2023)
This study is more focused on enhancing the accuracy of subject-verb agreement/ conjugation, by employing the mood analysis and self-correction techniques. The purpose of this study is to find out the effectiveness of mood analysis and self-correction practices to enhance EFL students’ conjugation accuracy. This research is an experimental study in a classroom context, which was carried out in the English Department of Stikubank University (UNISBANK) Semarang. Fifteen students played a role in an experimental group while fifteen others played a role in a control group. During the treatment, the experimental group did mood analysis and self-correction while the control group did not. The t-test calculation shows that there is a significant difference between the conjugation accuracy of the text written by the experimental group and that written by the control group. The experimental group outperformed the control group. The research findings indicate that mood analysis and self-correction practices are effective to enhance EFL students’ conjugation accuracy. Thus, it is recommended that practices of mood analysis and self-correction be applied in a teaching grammar lesson.